The safety and tolerability study of tiozonid in single dose with it increasing - A. U. Savchenko; G. V. Ramenskaya; M. S. Bourenkov (Качественная клиническая практика, 2018)
A study of the safety and tolerability tiozonid manufacturing by JSC «Pharm-Sintez» (Russia) at the single dose with it increasing (25, 200, 400 and 600 mg) in healthy volunteers. In each group, the volunteers were enrolled sequentially, based on the interim evaluation of safety parameters. This study was conducted in compliance with the requirements of legislation and the ethical principles set forth in the Federal Law «On Circulation of Medicines» (number 61-FZ of April 12, 2010), the Declaration of Helsinki of the World Medical Association (1964, with subsequent amendments), GOST R 52379-2005 «Good clinical practice» The study drug tiozonid manufacturing by JSC «Pharm-Sintez» (Russia) has shown a sufficiently high safety and well-tolerated at single oral doses in the range of 25-600 mg.